2021
DOI: 10.1155/2021/5597401
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotic Supplement Preparation Relieves Test Anxiety by Regulating Intestinal Microbiota in College Students

Abstract: Test anxiety creates barriers to learning and performance, which further affects students' social, behavioural, and emotional development. Currently, the medication to treat test anxiety has not been reported yet. Here, we enrolled 120 students to evaluate the effect of probiotic supplement preparation (PSP) on test anxiety from the aspect of the intestinal microbiota. We found that the intake of PSP alleviated the symptoms of depression and anxiety in students with test anxiety by evaluating their mental stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The WHO estimates that almost 450 million people all over the world suffer from stress-related disorders [ 34 ]. Independently from the COVID-19 pandemic, exams are the main sources of stress for students at Medical Universities, and test anxiety may affect about 20–40% of students [ 35 ]. It was found that during the exams, students often suffer from headaches, which were one of the most common reasons to take OTC drugs, such as analgesics [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO estimates that almost 450 million people all over the world suffer from stress-related disorders [ 34 ]. Independently from the COVID-19 pandemic, exams are the main sources of stress for students at Medical Universities, and test anxiety may affect about 20–40% of students [ 35 ]. It was found that during the exams, students often suffer from headaches, which were one of the most common reasons to take OTC drugs, such as analgesics [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Test anxiety, characterized by feelings of failure, tension, and worrying when an individual faces a vital test for promoting, occurs prevalently among college students. We reported that about 20%-40% of college students suffer from test anxiety in our previous study ( 1 ), and prolonged test anxiety is often accompanied by depression and insomnia, harming students’ physical and psychological health and even lead to suicide. Various examinations can represent a frequent and significant source of student’s anxiety ( 2 ).…”
Section: Introductionmentioning
confidence: 94%
“…Most patients experience abdominal distension, abdominal pain, or other abdominal discomfort and changes in defecation habits such as stool property or frequency) [ 1 4 ]. IBS has a high incidence in young adults, a long course of disease, and difficult recovery, which poses a great threat to the physical and mental health and quality of life of patients [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%